Factores de riesgo, protectores y funcionalidad familiar en pacientes sintomáticos respiratorios para presentar tuberculosis pulmonar, Arcapamba-Huertas 2016. - Ojeda Becerra, María de los Ángeles (2017)
El Oro, is the third province with more cases in Ecuador with pulmonary tuberculosis, the lack of respiratory symptomatology is a frequent problem and one of the greatest difficulties in controlling the disease. The objective of the present study was to evaluate the association between the risk factors, protective factors and family functionality of symptomatic respiratory patients aged 20 to 64 years to present pulmonary tuberculosis in the Arcapamba and Huertas parishes of Zaruma, 2016. It is descriptive prospective, analytical, correlational, which included 147 symptomatic respiratory. We analyzed variables such as age, sex, origin, occupation, overcrowding, housing ventilation, and satisfaction of basic needs, smoking, alcoholism, concomitant chronic diseases, and previous contact with tuberculosis patients, family functionality. Once each variable was characterized the coding and recoding was performed with the statistical program SPSS v16. 6,1% presented positive bacilloscopy. Of these 9 patients, 77,7% live in Huertas parish and 22,3% are from the Arcapamba parish. Male patients predominated with 88,8%. It was found as risk factors for pulmonary tuberculosis in subjects exposed to Koch's bacillus. Family function as a risk factor and / or protector is not dependent on the occurrence of pulmonary tuberculosis. Therefore, pulmonary tuberculosis remains a health problem in the area of primary care, since the risk factors are latent and have prevented its elimination, although fewer cases are reported, it is possible that in the medium term with the intervention Of family medicine will achieve better results. Key words: Infection, risk, protection, family, factors.